Free software applied to industrial drawing: the Blender case - Chung Pinzás, Alfonso Ramón (2009)
The article pretends to give an answer to the following problematic question how to maintain up to date an industrial drawing laboratory in software considering the economics restrictions that can be a university?. For this, it review free software alternatives and analyze the implementation of one of them call Blender. The results it traduce in a high acceptation grade of this software in the students, it can see in the students comment and results of their tests.